Échanges lexiculturels dans le domaine des fêtes et de la gas-tronomie: problèmes traductologiques et traitement lexicogra-phique (fr.-esp./esp.-fr.) - Mª Mercedes Eurrutia Cavero (Çédille: Revista de Estudios Franceses, 2013)
The present study analyzes the transla-tion problems posed by the socio-cultural nuances implicit in the lexicon of two key branches of the tourism sector: feasts and gastronomy. Bearing in mind an initial hypothesis by which You will leave the hypothesis cultural penetration within a language lacks uniformity, lexical asymmetries are most observed in linguistic interac-tions featuring an insufficient knowledge of the other’s culture. From Galisson’s standpoint (1991), I will explore the semantic changes occurring in the process of creation of neologisms as well as the socio-cultural factors underlying them. The absence of discourse equivalents will lead us to bring new approaches stemming in a bilingual lexicographic methodology.